Assessment of Ecological Risk of Soil in Rapid Urbanization Area by Risk Regionalization. Issue 1 (March 2021) - Zhao, Run; Li, Ning
Abstract: Rapid urbanization is a major source of environmental risk in soil. In this study, we developed the method of the potential ecological risk assessment, and investigated risk sources and soil pollution in a typical rapid urbanization area in Tianjin City, China. The proposed method was used to evaluate the level and spatial distribution of ecological risk of soil. Results show that the maximum of RI in all 114 sampling points was 1437.37, and four sampling points had RI exceeding 600, indicating extreme risk level. Moreover, the mean value of RI was 227.17, which was in moderate risk level. Among 10 heavy metals, Cd was the metal element that exhibited the most serious harm to the ecological environment, and reached high and extreme levels.